The interaction of Munc18-1 helix 11 and 12 with the central region of the VAMP2 SNARE motif is essential for SNARE templating and synaptic transmission - André, Timon; Classen, Jessica; Brenner, Philipp; Betts, Matthew J.; Dörr, Bernhard; Kreye, Susanne; Zuidinga, Birte; Meijer, Marieke; Russell, Robert B.; Verhage, Matthijs; Söllner, Thomas (eNeuro, 2020)
Sec1/Munc18 proteins play a key role in initiating the assembly of N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes, the molecular fusion machinery. Employing comparative structure modeling, site specific crosslinking by single amino acid substitutions with the photoactivatable unnatural amino acid p-Benzoyl-phenylalanine (Bpa) and reconstituted vesicle docking/fusion assays, we mapped the binding interface between Munc18-1 and the neuronal v-SNARE VAMP2 with single amino acid resolution. Our results show that helices 11 and 12 of domain 3a in Munc18-1 interact with the VAMP2 SNARE motif covering the region from layers À4 to 15. Residue Q301 in helix 11 plays a pivotal role in VAMP2 binding and template complex formation. A VAMP2 binding deficient mutant, Munc18-1 Q301D, does not stimulate lipid mixing in a reconstituted fusion assay. The neuronal SNARE-organizer Munc13-1, which also binds VAMP2, does not bypass the requirement for the Munc18-1·VAMP2 interaction. Importantly, Munc18-1 Q301D expression in Munc18-1 deficient neurons severely reduces synaptic transmission, demonstrating the physiological significance of the Munc18-1·VAMP2 interaction.
Gesehen am 18.01.2021